2017
DOI: 10.6002/ect.tond16.l12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Primary liver cancer is the fifth most common cancer overall and the second most common cause of cancer mortality worldwide. Hepatocellular carcinoma accounts for up to 90% of all primary hepatic malignancies and represents a major international health problem. It is a complex and heterogeneous malignancy, frequently occurs in the setting of a chronically diseased organ, and has multiple confounding factors. Liver transplant for hepatocellular carcinoma has been established as a standard treatment in selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Unlike macrovascular invasion, which can be diagnosed by imaging, microvascular invasion (MVI) is a histological finding that can only be diagnosed pathologically after surgery [ 4 ]. In the presence of MVI, tumor cells can spread within the liver, eventually forming multiple lesions in the liver, portal vein cancer thrombosis, or distant metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike macrovascular invasion, which can be diagnosed by imaging, microvascular invasion (MVI) is a histological finding that can only be diagnosed pathologically after surgery [ 4 ]. In the presence of MVI, tumor cells can spread within the liver, eventually forming multiple lesions in the liver, portal vein cancer thrombosis, or distant metastases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the histopathological grading of PHC is related to its degree of infiltration and distant metastasis and is the main influencing factor for its prognosis [ 5 ]. Thus, early diagnosis, accurate pathological grading, and timely treatment of PHC are the keys to prolonging the survival time of patients with liver cancer [ 6 ]. A hepatic biopsy is currently the gold standard for pathological grading of PHC.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) refers to a prevalent and lethal carcinoma classified under chronic hepatic disorders that leads to an unfavorable prognostic aftermath and high mortality [ 1 , 2 ]. As a complicated tumor with heterogeneity, HCC accounts for almost 90% of primary liver neoplasms has emerged as a challenging dilemma and health burden worldwide [ 3 ]. HCC is a unique cancer that typically arises from chronic liver disease, and its incidence rate depends on the complex interaction among the host, disease and environmental factors, and chronic hepatitis B or C virus infection is the main risk factor worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%